Treatment with a Catalytic Superoxide Dismutase (SOD) Mimetic Improves Liver Steatosis, Insulin Sensitivity, and Inflammation in Obesity-Induced Type 2 Diabetes - Gina M. Coudriet; Meghan M. Delmastro-Greenwood; Dana M. Previte; Meghan L. Marré; Erin C. O'Connor; Elizabeth A. Novak; Garret Vincent; Kevin P. Mollen; Sojin Lee; H. Henry Dong; Jon D. Piganelli (MDPI AG, 2017)
Oxidative stress and persistent inflammation are exaggerated through chronic over-nutrition and a sedentary lifestyle, resulting in insulin resistance. In type 2 diabetes (T2D), impaired insulin signaling leads to hyperglycemia and long-term complications, including metabolic liver dysfunction, resulting in non-alcoholic fatty liver disease (NAFLD). The manganese metalloporphyrin superoxide dismustase (SOD) mimetic, manganese (III) meso-tetrakis (N-ethylpyridinium-2-yl) porphyrin (MnP), is an oxidoreductase known to scavenge reactive oxygen species (ROS) and decrease pro-inflammatory cytokine production, by inhibiting nuclear factor kappa-light-chain-enhancer of activated B cells (NF-κB) activation. We hypothesized that targeting oxidative stress-induced inflammation with MnP would assuage liver complications and enhance insulin sensitivity and glucose tolerance in a high-fat diet (HFD)-induced mouse model of T2D. During 12 weeks of feeding, we saw significant improvements in weight, hepatic steatosis, and biomarkers of liver dysfunction with redox modulation by MnP treatment in HFD-fed mice. Additionally, MnP treatment improved insulin sensitivity and glucose tolerance, while reducing serum insulin and leptin levels. We attribute these effects to redox modulation and inhibition of hepatic NF-κB activation, resulting in diminished ROS and pro-inflammatory cytokine production. This study highlights the importance of controlling oxidative stress and secondary inflammation in obesity-mediated insulin resistance and T2D. Our data confirm the role of NF-κB-mediated inflammation in the development of T2D, and demonstrate the efficacy of MnP in preventing the progression to disease by specifically improving liver pathology and hepatic insulin resistance in obesity.